Management of respiratory tract infections in young children—A qualitative study of primary care providers’ perspectives - Ruby Biezen (Nature Portfolio, 2017)
Respiratory tract infections: Clinicians swayed by parental anxiety and pressure The emotions and psychology of both parents and clinicians influence how respiratory tract infections (RTIs) are managed in young children. Researchers in Australia, led by Ruby Biezen from Monash University, interviewed 30 primary care clinicians about their views on how to care for children with RTIs, such as the common cold. The interviews focused on symptomatic management, over-the-counter medications and antibiotic use. Despite the availability of best-practice guidelines, clinicians did not always follow the recommendations owing to factors such as time constraints, parental anxiety, perceived parental pressure, and fear of losing patients. These are some of the reasons why clinicians sometimes advise or prescribe unnecessary medications. The authors suggest that a team approach involving multiple healthcare professionals who deliver consistent advice could improve guideline adherence.